Keberkesanan gaya kepimpinan kepolisan: Kajian kes terhadap Ketua Polis Negara (KPN) Malaysia ke-14 - Zulkifli, Othman (2025)
This study analyzes the effectiveness of the 14th Inspector General of Police's (IGP) leadership style in leading the Royal Malaysia Police (RMP). The objectives of the study are to identify the characteristics of the 14th IGP's leadership style, assess its impact on organizational performance and public trust, and examine the suitability of this leadership style in developing future RMP leadership models. This study employs a qualitative method with a case study design, involving in-depth interviews with four senior RMP officers, document analysis, and non-participant observation at the Police Headquarters in Bukit Aman. The findings indicate that the 14th IGP practices a transformational-situational leadership style adapted to the local context. This leadership style has proven effective in enhancing organizational performance, building public trust, and increasing motivation among police personnel. This leadership model can serve as a foundation for developing training programs and leadership selection processes within the RMP. The main implication of this study lies in developing a more robust and relevant leadership model for the RMP to address future challenges. Despite limitations such as a small sample size and a narrow research scope, this study contributes to the body of literature on leadership within the law enforcement context in Malaysia and the broader Southeast Asian region. Further research should consider longitudinal studies and an expanded scope at the contingent and district levels.